EXPLORING UNIVERSITY STUDENTS’ PERCEPTIONS OF ACADEMIC READING: A QUALITATIVE STUDY IN MALAYSIA - Ahmad Azmi AbdelHamid Esmaeil; Dg Norizah Ag Kiflee@Dzulkifli; Ismail Maakip; Murnizam Halik; Sanen Marshall; Mazni Mustapha; Lailawati Madlan@Endalan (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Reading academic textbooks offers numerous benefits to university students, such as enhancing their knowledge, fostering critical thinking, and promoting classroom engagement. Despite these advantages, there is a dearth of research investigating students’ perceptions of textbook use, particularly in a Malaysian context. To address this gap, the current study aims to explore student perceptions at a Malaysian university. Employing a qualitative research methodology, the study gathered data through reflection papers written by students on the subject matter, which were subsequently analyzed using a thematic approach. Two main themes emerged: the ’Importance of Reading’ and the ’Constraints of Reading.’ The former theme encompassed elements such as knowledge enhancement, critical thinking, and career development, as well as aiding performance in exams and assignments. Conversely, the latter theme revealed constraints like a lack of encouragement from educators, the. perception that books are non-essential, and barriers related to time, finances, language proficiency, and limited capabilities. Additionally, some students expressed concerns that relying too heavily on textbooks could restrict their intellectual freedom. These issues are elaborated further in the discussion section of the paper.